Em pauta: Veja, Tempo e as representações de África - Conceição, Juvenal de Carvalho (2019)
This paper analyzes the historicity of Africa representations in the press, specifically in information magazines. The concern of historians with the "how Africa is portrayed" comes from further afield. The sources used are reports of travelers, merchants, missionaries and all kinds of agents colonizing, through literature, poetry, textbooks, popular tales, photography to the cinema and the press, which in the twentieth century became one of the main vehicles in the contest for the conviction and adherence to values and beliefs. The thesis that I try to demonstrate is that the representations of Africa in the press integrate the strategies of construction of the "Other", the "Different", the "inferiorized" as part of the establishment of Western hegemony and power relations in Brazil. For that purpose, a corpus of analysis was formed by the set of pieces published in the magazines Veja, Istoé and Época, which refer to the African continent, from the beginning of the circulation of these weekly newspapers, in 1968, 1976, 1998, respectively, until the year of 2013 when Nelson Mandela passed away. Also added was the magazine Tempo, a Mozambican publication that circulated from 1970 onwards. The selected pieces are analyzed from categories such as representation, in the line of reading made by Stuart Hall; structural racism and hegemony. The comparative analysis between the Brazilian and Mozambican publications is taken to capture dominant contents, silences, omissions and changes of focus revealing the role of these information magazines in the dispute over hegemony through representations of Africa as a decisive, structuring cultural element of power relations